Ethereal Lenscraft Company Profile UI/UX Design Using Design Thinking Approach - Azis, Zulkifli; Sugianto, Rulliansyah (JISA(Jurnal Informatika dan Sains), 2025)
Ethereal Lenscraft is a company specializing in photography and videography, with its company profile designed to effectively market its services. The primary focus of the website is to enhance user interactivity and satisfaction for those seeking documentation services for their events. Therefore, it is essential to conduct research from a design perspective, particularly in terms of UI/UX. This study employs the Design Thinking methodology to enhance the user interface (UI) and user experience (UX) of the "Ethereal Lenscraft" website, which offers photography and videography services tailored to specific events. The research follows the Design Thinking steps, including empathy, definition, ideation, prototyping, and testing, to ensure that the user experience aligns with expectations and leaves a lasting impression. Additionally, the photography industry entails technical complexities and various supporting elements, including equipment and personnel. Photography and videography works are categorized into commercial, journalistic, and artistic/expression genres. The outcomes of this study will serve as a benchmark for enhancing user experience and fostering deeper interactions on the "Ethereal Lenscraft" company profile website.